Assessing Website Usability Attributes - Nur Sukinah, Aziz; Adzhar, Kamaludin; Azliza, Yacob; Noor Suhana, Sulaiman (AENSI Publishing, 2014)
Web sites are widely used in daily life no matter for work or for entertainment, and connect with others in their social life. Usability is one of the quality factors that determine the successfulness of a web site. This study reviews existing usability standards and model from previous studies. Most of the previous works only mentioned the attribute of usability in general and no details discussion is included. There are less published works in usability guidelines that comes up with metric for easy measurement especially focusing for web site. This study identifies the major elementsin web site usability from the previous studies and usability standards. It adapted Quality in Use Intergrated Measurement Model or QUIM model that include accessibility in web site usability unlike earlier work which separate between usability and accessibility. The results show effectiveness, efficiency, learnability, satisfaction and accessibility have significant impacts and highly correlated on web site usability. These attributes should needs to be consider when designing web site.